Answer:
John need to remove <u>4760 cubic feet</u> of dirt.
Step-by-step explanation:
Given:
John is digging a hole for a swimming pool,the hole will be 28 feet long, 5 feet wide, 34 feet wide.
Now, to find the cubic feet of dirt John need to remove.
Length = 28 feet.
Width = 5 feet.
Height = 34 feet.
<u><em>As the swimming pool is in the shape of a rectangular prism.</em></u>
So, we put formula of volume to get the cubic feet of dirt need to remove:
![Volume = length\times width\times height](https://tex.z-dn.net/?f=Volume%20%3D%20length%5Ctimes%20width%5Ctimes%20height)
![Volume=28\times 5\times 34](https://tex.z-dn.net/?f=Volume%3D28%5Ctimes%205%5Ctimes%2034)
![Volume=4760\ cubic\ feet.](https://tex.z-dn.net/?f=Volume%3D4760%5C%20cubic%5C%20feet.)
Therefore, John need to remove 4760 cubic feet of dirt.
Answer: 115 is the answer
Step-by-step explanation:
Finding the mean is you have to add it all up:
49+55+52+46+47+42+38= 328
The divide it by the amount of numbers so, 329/7= 47.
Subtract 47 from every number then, but even if you get a negative number you gotta keep it a positive so just ignore it if you get a negative answer when subtracting, once you do that you would add up those answers you got so;
2+8+5+1+0+5+9= 30
Then divide it again, 30/7
Which then you get the M.A.D which is 4.3, rounded to the nearest ten.
Answer:
![y=-3x+4](https://tex.z-dn.net/?f=y%3D-3x%2B4)
Step-by-step explanation:
To get the equation in the slope-intercept form first, put the equation in slope-point form using the information given. The slope-point form is
. Then solve for y.
Distribute -3 to
,
![y-(-2)=-3x+6](https://tex.z-dn.net/?f=y-%28-2%29%3D-3x%2B6)
Then, add -2 to both sides,
![y=-3x+4](https://tex.z-dn.net/?f=y%3D-3x%2B4)
This is your final answer; the slope is -3 and the y-intercept is 4. There are also a few other ways to solve but I find this the easiest.
Answer:
x = 1/3
Step-by-step explanation:
f(x) = -3x^2 + 2x-17
This is in the form
ax^2 +bx+c
a = -3 b = 2 c = -17
The axis of symmetry is at
x = -b/2a
x = -2/ (2*-3)
x = -2/-6
x = 1/3